An Extreme Mountain Ultra-Marathon Decreases the Cost of Uphill Walking and Running - Vernillo, Gianluca; Savoldelli, Aldo; Skafidas, Spyros; Zignoli, Andrea; La Torre, Antonio; Pellegrini, Barbara; Giardini, Guido; Trabucchi, Pietro; Millet, Grégoire P.; Schena, Federico (Frontiers in Physiology, 2016)
Purpose: To examine the effects of the world’s most challenging mountain ultramarathon (MUM, 330 km, cumulative elevation gain of +24000 m) on the energy cost and kinematics of different uphill gaits. Methods: Before (PRE) and immediately after (POST) the competition, 19 male athletes performed three submaximal 5-min treadmill exercise trials in a randomized order: walking at 5 km·h-1, +20%; running at 6 km·h-1, +15%; and running at 8 km·h-1, +10%. During the three trials, energy cost was assessed using an indirect calorimetry system and spatiotemporal gait parameters were acquired with a floor-level high-density photoelectric cells system. Results: The average time of the study participants to complete the MUM was 129 h 43 min 48 s (range: 107 h 29 min 24 s to 144 h 21 min 0 s). Energy costs in walking (-11.5 ± 5.5%, P < 0.001), as well as in the first (-7.2 ± 3.1%, P = 0.01) and second (-7.0 ± 3.9%, P = 0.02) running condition decreased between PRE and POST, with a reduction both in the heart rate (-11.3%, -10.0%, and -9.3%, respectively) and oxygen uptake only for the walking condition (-6.5%). No consistent and significant changes in the kinematics variables were detected (P values from 0.10 to 0.96). Conclusion: Though fatigued after completing the MUM, the subjects were still able to maintain their uphill locomotion patterns noted at PRE. The decrease (improvement) in the energy costs was likely due to the prolonged and repetitive walking/running, reflecting a generic improvement in the mechanical efficiency of locomotion after 130 h of uphill locomotion rather than constraints imposed by the activity on the musculoskeletal structure and function.